2015
DOI: 10.3762/bjnano.6.259
|View full text |Cite
|
Sign up to set email alerts
|

Chemiresistive/SERS dual sensor based on densely packed gold nanoparticles

Abstract: SummaryChemiresistors are a class of sensitive electrical devices capable of detecting (bio)chemicals by simply monitoring electrical resistance. Sensing based on surface enhanced Raman scattering (SERS) represents a radically different approach, in which molecules are optically detected according to their vibrational spectroscopic fingerprint. Despite different concepts are involved, one can find in the literature examples from both categories reporting sensors made of gold nanoparticles. The same building bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…Therefore, there is urgent need to develop a fast, convenient, highly selective and sensitive ammonia sensor that can detect low concentrations of ammonia in air, which is critical for environmental monitoring. A lot of work has been reported in the literature for the detection of toxic and explosive gases using various oxides such as α-Fe 2 O 3 , ZnO, SnO 2 , WO 3 , NiO, In 2 O 3 , and so forth owing to their several advantages such as high sensitivity to a large variety of gases, low detection limit, fast response and recovery, superb stability, low fabrication cost, and simple preparation. , However, the oxide-based materials require external stimuli such as high temperature, ultraviolet (UV) light activation, and so forth for the sensor response and/or recovery, which restricts their further application. Hence, these materials are power-consuming sensors. Therefore, great efforts are being taken to solve the great challenge by developing advanced sensors that can effectively detect ammonia at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is urgent need to develop a fast, convenient, highly selective and sensitive ammonia sensor that can detect low concentrations of ammonia in air, which is critical for environmental monitoring. A lot of work has been reported in the literature for the detection of toxic and explosive gases using various oxides such as α-Fe 2 O 3 , ZnO, SnO 2 , WO 3 , NiO, In 2 O 3 , and so forth owing to their several advantages such as high sensitivity to a large variety of gases, low detection limit, fast response and recovery, superb stability, low fabrication cost, and simple preparation. , However, the oxide-based materials require external stimuli such as high temperature, ultraviolet (UV) light activation, and so forth for the sensor response and/or recovery, which restricts their further application. Hence, these materials are power-consuming sensors. Therefore, great efforts are being taken to solve the great challenge by developing advanced sensors that can effectively detect ammonia at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…It is also interesting to note that gold surfaces are preferred over silver for many EC-SERS applications due to their wider hydrogen overpotential and, thus, a wider range of operational potentials and higher overall chemical and electrochemical inertness. Finally, as demonstrated by previous works, such self-assembled nanoparticle films could also be used for electrical resistance-based chemical sensing [47] or deformation sensing [48], pointing toward interesting possibilities for developing multi-stimuli-responsive sensing devices.…”
Section: Au Np Films As Electrodes For Ec-sers Assaysmentioning
confidence: 63%
“…For instance, Boca et al have demonstrated dual signal-based electrical/optical proof of concept biosensing prototype exploiting the nano-gaps formed during the self-assembly of AuNPs. This showed excellent SERS capabilities and chemi-resistivity of nano-gap AuNPs for the detection of 4-mercaptophenyl boronic acid (Boca et al 2015). In another report, an aptamer-based AuNP-functionalized biosensor has been developed showing high sensitivity (20 nM) for biomolecular analysis using avidin as a model compound.…”
Section: Sensors and Biosensorsmentioning
confidence: 99%